2018
DOI: 10.1186/s12884-018-2012-x
|View full text |Cite
|
Sign up to set email alerts
|

Should prenatal care providers offer pregnancy options counseling?

Abstract: BackgroundProfessional guidelines indicate that pregnancy options counseling should be offered to pregnant women, in particular those experiencing an unintended pregnancy. However, research on whether pregnancy options counseling would benefit women as they enter prenatal care is limited. This study examines which women might benefit from options counseling during early prenatal care and whether women are interested in receiving counseling from their prenatal care provider.MethodsAt four prenatal care faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…We also aimed to: 1) Understand women's experiences considering and seeking abortions in a state with multiple versus few restrictive abortion policies; 2) Assess health & social service needs of women who consider but do not have abortions; and 3) Understand women's experience with and impacts of Pregnancy Resource Centers. We have previously published some findings related to each aim [5,8,[22][23][24]]. The analyses presented in this manuscript are a-priori components of the first aim.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also aimed to: 1) Understand women's experiences considering and seeking abortions in a state with multiple versus few restrictive abortion policies; 2) Assess health & social service needs of women who consider but do not have abortions; and 3) Understand women's experience with and impacts of Pregnancy Resource Centers. We have previously published some findings related to each aim [5,8,[22][23][24]]. The analyses presented in this manuscript are a-priori components of the first aim.…”
Section: Methodsmentioning
confidence: 99%
“…In this mixed-methods study, quantitative and qualitative data collections were convergent and embedded (Fig 1). Study methods have been described in detail previously [5,8,22,23]. Briefly, we recruited 589 English and Spanish-speaking pregnant women 18 years and older at their first prenatal care visit at three prenatal care facilities in Southern Louisiana and one prenatal care facility in Baltimore, Maryland between June 2015 and June 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Our finding that women who reported a policy barrier to abortion were more likely to report need for pregnancy options counseling, substance use treatment, and intimate partner violence counseling/ shelter is also consistent with prior research. As part of our larger study, we found that, although most women are certain of their decision to continue their pregnancy upon entering prenatal care, there is a subset who are uncertain and wish to discuss their options with their prenatal care provider (Berglas, Williams, Mark, & Roberts, 2018b). Intimate partner violence is a known reason that some women decide to terminate their pregnancy, expressing concern that they would be tied to an abusive partner and that their child would be exposed to violence (Biggs et al, 2013; * Job counseling, transportation assistance, quit smoking, dental care, and child care were asked among women in Maryland only.…”
Section: Discussionmentioning
confidence: 94%
“…Our finding that all options counseling was associated with better patient experience corroborates prior qualitative research that indicated patients prefer all-options counseling. For example, a study of patients entering prenatal care found that a broad majority of patients were open to discussing pregnancy options, whether or not their pregnancy was intended [36]. Another qualitative study of options counseling preferences, which included both patients in prenatal care and women seeking abortion services, found patients preferred that providers: 1) respect patient autonomy, 2) avoid assumptions about patients' desired pregnancy outcomes, and 3) consider the needs of the patient beyond her pregnancy [16].…”
Section: Discussionmentioning
confidence: 99%